Erratum: Elaphidiini (Coleoptera, Cerambycidae) from the Caribbean region of Colombia: New species, taxonomic notes and new geographical records - García, Kimberly; Nascimento, Francisco Eriberto de Lima (Papéis Avulsos de Zoologia, 2020)
Two new species of Elaphidiini from Colombia are described: Sphaerion costae sp. nov., and Mephritus costae sp. nov. The keys to species of Sphaerion Audinet-Serville, 1834 and Mephritus Pascoe, 1866 are translated and modified to include the new species. Chromatic variations of Mephritus apicatus (Linsley, 1935) are reported. Moreover, the geographical distribution is expanded for 12 species of Elaphidiini.